2005
DOI: 10.1111/j.1365-246x.2005.02577.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of soil type on the magnetic susceptibility measured throughout soil profiles

Abstract: SUMMARY The interpretation of soil susceptibility measurements depends on knowledge of a reference value. This reference value will be influenced by the type of soil. In the present study, data of various soil types, which formed on diverse parent material, are analysed. As the same data set has been used in a soil pollution study, we are able to estimate and exclude the influence of pollution. Susceptibility values of unpolluted soils turn out to significantly depend on the soil type. Chernozem samples yield … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(87 citation statements)
references
References 26 publications
5
81
1
Order By: Relevance
“…Correlation coefficients between magnetic parameters and the other available parameters are listed in Table 4. Some groups did not yield significant results, mainly because of the small number of available samples (Hanesch and Scholger, 2005).…”
Section: Correlation Between Magnetic and Pedological Parametersmentioning
confidence: 97%
See 2 more Smart Citations
“…Correlation coefficients between magnetic parameters and the other available parameters are listed in Table 4. Some groups did not yield significant results, mainly because of the small number of available samples (Hanesch and Scholger, 2005).…”
Section: Correlation Between Magnetic and Pedological Parametersmentioning
confidence: 97%
“…The ratios between magnetic and pedological parameters have been examined by many authors, such as Hanesch and Scholger (2005), Jordanova et al (2010) and Maher (1998). Correlation coefficients between magnetic parameters and the other available parameters are listed in Table 4.…”
Section: Correlation Between Magnetic and Pedological Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Hanesch and Scholger (2005) (Jordanova and Jordanova, 1999). The transformation of goethite or ferrihydrite to maghemite takes part during heating (Nørnberg et al, 2004) at temperatures as low as 220°C (Sidhu, 1988).…”
Section: Charred Organic Matter As Colouring Agentmentioning
confidence: 99%
“…The mapping of the MS has stood out as one of the more indirect methods used for agricultural studies (SIQUEIRA et al, 2010b) and environmental characterization (GRIMLEY et al, 2004). Some studies reported the relation between MS and the loss of soil by erosion (HANESCH & SCHOLGER, 2005;VENTURA JR. et al, 2001;PARSONS et al, 2010) and the identification of areas with different erosion potentials (ROYALL, 2001) .…”
Section: Introductionmentioning
confidence: 99%